Zygophylax biarmata Billard 1905 - Gu, Zhangjie; Ruthensteiner, Bernhard; Moura, Carlos J.; Liu, Lihua; Zhang, Rui; Song, Xikun (Zenodo, 2022)
ZYGOPHYLAX BIARMATA BILLARD, 1905 (FIG. 7) Zygophylax biarmata : Ramil & Vervoort, 1992: 59–65, figs 11e–h, 12a–i, 13e, f (synonymy). Type locality: Bay of Biscay, north-east Atlantic; 411 m. Specimens examined: Three colonies from the Gulf of Cadiz, one fertile; see details in Supporting Information, Table S1. Molecular sequences: 16S rRNA gene (Moura et al. , 2008, 2012); see sequence details in Supporting Information, Table S3. Measurements: See Supporting Information, Table S2. Description: Trophosome. Colonies upright, about 0.9 cm high (Fig. 7A). Hydrocaulus geniculate, polysiphonic, unsegmented, branching regularly (Fig. 7A, B). Hydrocladia coplanar, forming angles of 60°– 90° with the hydrocaulus (Fig. 7B), dichotomously branched, mono- or polysiphonic, with irregular nodes (Fig. 7B, C), axillary hydrothecae present at the branching sites (Fig. 7D). Hydrothecae alternating regularly in one plane, forming angles of 60°–90° with the longitudinal axes of the corresponding hydrocladia (Fig. 7C), short-pedicellate, tubular, the distal part straight or curved away from the internode and forming angles of about 30° with the proximal part; diaphragm oblique, margin slightly everted, with two to seven renovations (Fig. 7C, E, G). A tubular nematotheca present at apophyses of hydrocladia, with one to six renovations (Fig. 7C, E, F). Gonosome: Gonothecae clustering into coppiniae on hydrocaulus (Fig. 7A, B); coppiniae with dichotomously branched defensive tubes and hydrothecae. The morphology of individual gonothecae could not be established properly without destructive methods, and the coppiniae in the present material are obscured by adhering particles, not allowing a detailed examination to be done. Distribution: Gulf of Cadiz (Moura et al. , 2012; this study); Bay of Biscay north-west of Spain; the Azores; Madeira; the Canary Islands; the east coast of South Africa; the Madagascar area; the Zanzibar area (See Ramil & Vervoort, 1992). Published as part of Gu, Zhangjie, Ruthensteiner, Bernhard, Moura, ...